1998
DOI: 10.1111/j.1475-2743.1998.tb00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Measured and simulated availability and leaching of nitrogen associated with frequent use of catch crops

Abstract: Abstract. Results are presented from three years (1992‐1995) of a field leaching experiment on a sandy soil in south‐west Sweden. Plots of spring cereals, either with or without an undersown perennial ryegrass catch crop, were compared for nitrogen leaching and nitrogen status in soil. Both treatments were ploughed in spring, and other tillage regimes were also identical. Measurements of nitrogen leaching from drains, nitrogen uptake in crops and mineral nitrogen in the soil were made. Two coupled, simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 18 publications
3
35
0
1
Order By: Relevance
“…A first strategy is curative: catch crops sown after maize harvest or undersowed companion crops can capture residual N. However, due to the late harvest date of silage maize, N uptake by catch crops can be rather poor, particularly in cold autumns and winters (Aronsson and Torstensson, 1998;Castillon, 2000;Gall Le et al, 1997). Schröder et al (1996) found that nitrate leaching under cover cropped plots at high N rates exceeded leaching under fallow plots at low N rates.…”
Section: Introductionmentioning
confidence: 99%
“…A first strategy is curative: catch crops sown after maize harvest or undersowed companion crops can capture residual N. However, due to the late harvest date of silage maize, N uptake by catch crops can be rather poor, particularly in cold autumns and winters (Aronsson and Torstensson, 1998;Castillon, 2000;Gall Le et al, 1997). Schröder et al (1996) found that nitrate leaching under cover cropped plots at high N rates exceeded leaching under fallow plots at low N rates.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these options have been suggested as potential measures to reduce nutrient leakage from agriculture activities (Aronsson and Torstensson 1998, Kirchmann et al 2002, Arheimer et al 2004). The policy option for private sewers was to connect the private sewers to a larger sewage treatment plant.…”
Section: Conceptual Modelmentioning
confidence: 99%
“…The introduction of catch crops could mitigate N losses from soils (Martinez and Guiraud, 1990;Vos and Putten, 2001), but during the year there are always fallow periods or low crop growth phases where N is not taken up by plants (Rodrigues, et al, 2002). On the other hand, the progressive accumulation of soil organic matter could increase the risk of soil N losses (Lewan, 1994;Aronsson and Torstensson, 1998).…”
Section: Introductionmentioning
confidence: 99%